PRAKTIK PERTANIAN PADI MENGGUNAKAN METODE BAGI HASIL DALAM PERSPEKTIF EKONOMI ISLAM - Ricoh Herlambang (Khulasah : Islamic Studies Journal, 2023)
The practice of sharing agricultural products in Majasih Village, Sliyeg District, Indramayu Regency is known as "Sewan Sawah" in Islamic economics this activity is known as muzara'ah or mukhabarah. This profit-sharing practice contains elements of mutual help. Someone who owns land but does not have the opportunity to cultivate his land and on the other hand a cultivator has the ability and opportunity but does not have land to manage, so there needs to be cooperation between the two. The focus of this research is the practice of sharing agricultural produce or "Sewan Sawah" in Majasih Village, Sliyeg District, Indramayu Regency. This research method is a qualitative research with a normative approach. The data source for this research is primary data which the researchers obtained by interviewing land owners, sharecroppers and community leaders. For data processing and analysis techniques, namely data analysis by Miles and Huberman, namely data collection, data reduction, data presentation and drawing conclusions. While testing the data using data triangulation techniques and theoretical triangulation. The results of the study show that the practice of sharing agricultural products implemented by farming communities in Majasih Village, Sliyeg District, Indramayu Regency, is not contrary to the concept of Islamic economics, even though they make agreements and Karangwangikatan are not carried out in written form, this is influenced by a sense of shared trust and a sense of kinship as a form of social responsibility. In general, the agricultural profit-sharing system applied by the farming community of Majasih Village, Sliyeg District, Indramayu Regency, namely profit-sharing with a ratio of one-half to one-half and one-third to one-third, such a profit-sharing ratio was also practiced at the time of Rasulullah SAW.